African navies
1 online resource (x, 240 pages)
Keywords: "This edited volume focuses on aspects of the understudied theme of African sea-power, including African navies and the engagement of non-African navies with the continent. Africa possesses 48,000 kilometers of coastline, comprising 38 out of 54 of the continent's states and several strategic choke points for international shipping, such as the Suez Canal, the Gulf of Aden and the Cape of Good Hope. Nevertheless, post-colonial Africa's small navies and their relations with the navies of external powers have not received much scholarly attention. Focusing on Sub-Saharan Africa, this collection attempts to address this neglect and stimulate further research by offering original chapters related to historical and contemporary themes around Africa's navies. The historical chapters cover the origin of the Tanzanian, Ethiopian, Nigerian and Ghana navies during the era of decolonization and the Cold War, the asymmetrical naval campaign fought during the Nigerian Civil War (1967-70), and the activities of the Soviet Navy in supporting African states and movements fighting lingering colonialism and white supremacy during the 1970s and 1980s. Focusing on the contemporary situation, other chapters discuss the engagement of the Indian Navy with Africa, the potential role of the Angolan and Mozambican navies in the Southern African Development Community (SADC), the transformation and development of the post-apartheid South African Navy, and the challenges and capabilities of African navies in the early twenty-first century. The book concludes by discussing the question of whether African coastal countries need navies. This book will be of much interest to students of naval power, strategic studies, African politics and International Relations"--